Answer :

Rearranging the equations, we have

2x – y = - 3 …eq.1


3x – 7y = - 10 …eq.2


To solve these equations, we need to make one of the variables (in both the equations) have same coefficient.


Lets multiply eq.1 by 7, so that variable y in both the equations have same coefficient.


Recalling equations 1 & 2,


2x – y = - 3 [×7


3x – 7y = - 10


14x – 7y = - 21


3x – 7y = - 10


On solving the above two equations we get,


11x = - 11


x = - 1


Substitute x = - 1 in eq.1/eq.2, as per convenience of solving.


Thus, substituting in eq.1, we get


2( - 1) – y = - 3


- 2 – y = - 3


y = - 2 + 3


y = 1


Hence, we have x = - 1 and y = 1.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRS Aggarwal - Mathematics

If 2x – 3y = 7 anRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics